Re-peasantization of indigenous youth as a strategy for territorial defense in Chiapas - Chahim Huet Macz; Peter Rosset; Saraí Miranda Juárez; León Enrique Ávila Romero (Universidade Federal do Norte do Tocantins, 2023)
This document presents the results of a research study carried out with the objective of learning the perspective of young indigenous graduates of two university institutions with an intercultural approach in Chiapas, Mexico. Specifically, these young people were asked if after studying and finishing a university degree they returned to their communities or migrated, if they consider themselves peasants or not, if they continue dedicating time to agricultural or livestock production, and if they consider themselves defenders of their territories. With the participation of 46 young people from 40 communities and 9 indigenous groups, it was found that 83% consider themselves to be at least a little bit peasants since they continue to accompany their families in production on their lands or they themselves have agricultural projects, in addition to dedicating themselves to other diverse activities. The term re-peasantization is used to characterize the decision of young indigenous people to maintain a relationship with their land and their community despite the tendency to migrate to the cities, re-peasantization is understood as the struggle for autonomy in a hostile environment and a context of dependency.